Evaluation of the Knowledge and Behaviors of Gazi University Medical Faculty Students on Rational Use of Medicines (Turkey Health Literacy Journal, 2021)
Objective: The aim of this study was to evaluate the knowledge and behavior of Gazi University Faculty of Medicine students regarding rational use of medicines before graduation. Method: The population of the research, which was planned as a descriptive study, consists of 1st, 2nd, 3rd and 4th grade students of Gazi University Faculty of Medicine. A total of 145 students participated in the study, and an online questionnaire consisting of 33 questions on sociodemographic characteristics and rational drug use behaviors was conducted. SPSS-23 package program was used for statistical analysis of the data. In the descriptive statistics section, categorical variables were presented as numbers and percentages, and continuous variables were presented as mean ± standard deviation and median. Chi-square test was used in the comparison analyzes of categorical variables, and the statistical significance level was accepted as p<0.05. Results: 57.9% of the participants were female and 42.1% were male. The average age of the participants was found to be 20.99 years. 65.4% of women and 45.9% of men use medication without being ill, considering that it may be necessary. 66.7% of women and 49.2% of men have six or more unused or uncompleted medicines at home. Since the expiration date has passed, the tendency of the 4th grade students to throw away the drugs without even opening the box was found to be significantly higher than the others. Conclusion: Although students’ rational use of medicines behaviors are generally found to be high, it shows that there is a need for training on rational drug use in some subjects due to the fact that cold chain drugs are stored under incorrect conditions, the high number of drugs that are thrown away because of their expiration date is over and there are drug use behaviors without examination to physcian.